Exercise During Pregnancy Reduce Labor Anxiety - Diyan Indrayani; Titi Legiati; Ferina (Women, Midwives and Midwifery, 2023)
Background: Pregnancy and childbirth are meaningful experiences for a woman and therefore need to be prepared both physically and psychologically. Physical exercise is one of the methods used to psychologically and physically prepare pregnant women for a pleasant, healthy pregnancy and birth for both mother and child. Purpose:  The study aimed to find out the differences in the anxiety of pregnant women facing labor before and after doing exercise. Methods: The research was conducted in Bandung City and Regency. The research design employed a quasi-experimental pre-posttest. Samples were taken by consecutive sampling. The sample was pregnant women who meet the inclusion criteria for gestational age > 34 weeks, have no pregnancy complications and exercise (walking, yoga, jogging) twice per week for 30-60 minutes. The number of respondents was 60 people. The data obtained is primary data from the results of a questionnaire assessment about the anxiety of mothers facing childbirth as measured by the Hamilton Anxiety Rating Scale (HARS). The data analysis used is the normality test with Kolmogorov Smirnov and then it is continued  with Wilcoxon to analyze the differences in anxiety facing labor before and after exercise. Results: The results showed that there were differences in anxiety facing labor in pregnant women before and after exercising. The anxiety score before exercise is 55,5 and after exercise is 46,5. There were decrease anxiety score of 9 and p value <0,005 meaning that there were significant differences before and after exercise. Conclusion: Exercise during pregnancy can provides a relaxing effect and inhibit sympathetic nerve activity thereby reducing the level of anxiety in pregnant women in facing labor. It is recommended for pregnant women to do exercise regularly during pregnancy.